Immigrant Political Representation and Local Ethnic Concentration: Evidence from a Swedish Refugee Placement Program. Issue 3 (24th July 2022) - Lindgren, Karl-Oskar; Nicholson, Michael D.; Oskarsson, Sven
Abstract: This study leverages population registry data from Sweden to examine whether immigrants who live in areas with a high concentration of ethnic minorities are more or less likely to be nominated for political office. It exploits a refugee placement program in place in Sweden during the late 1980s and early 1990s that restricted refugees' opportunities to freely choose their place of residence. The article presents evidence that immigrants who live in areas with a high ethnic density are less likely to be nominated for political office. The findings have important implications for local integration policies as well as refugee placement policies, as many countries consider local context when resettling refugees.